(3MbGFb CSQGQ GdCWHGAs - (3eSYhO Hf eMeO, GdSfLQjs
(3ChdgG (B:s
(3hHYO , aEf GdYHO eSYhO Hf eMeO GdSfLQi GdWHjH , habI Gddg JYGdi dUGOb GdCbhGd hUGdM GdCMhGd s
(3BNQgG (B:s
(3GdQcHI KeGfjI YVdGJ GdbOe SHY YVdGJ , GdCUGHY GKfG hYTQhf YVdI s
(3QSe GdhRjQ bGSe CHj GdaGNQ Hf LYaQ ai JHjf GdCSeGA GdGUWdGMGJ Ydi SHjd GdQSe hGdJMOjOs
(3hQJHg Ydi KdGKg afhfs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3LeY s
Keywords: (3GdWHs